Ambient Air Condition for Room‐Temperature Deposition of MAPbI3 Films in Highly Efficient Solar Cells. Issue 45 (7th October 2018) - Yang, Zijiang; Pan, Jinlong; Liang, Yongqi; Li, Qi; Xu, Dongsheng
Abstract: The power conversion efficiency of perovskite solar cells has been boosted rapidly, it has so far exceeded that of commercial polycrystalline silicon solar cells. This has prompted great interest in large‐scale production and deployment of perovskite solar cells. However, state‐of‐the‐art perovskite solar cells are fabricated inside gloveboxes and further annealing at high temperatures (typically at >100 °C for 30 min) is needed. These two required conditions are not compatible with, either in the respect to high‐throughput or thermal budget, a feasible industrial production process. By eliminating the two requirements, the deposition of perovskite films both at room temperature and under ambient air condition will make the scalable roll‐to‐roll fabrication scheme feasible. Here, the anti‐solvent (chloroform) washing is introduced to the previously developed hydrochloride‐assisted method and demonstrate that the room‐temperature method can be carried out under ambient air condition for MAPbI3 film deposition. Through this new procedure, a power conversion efficiency as high as 17.72% is achieved for MAPbI3 planar devices fabricated under a relative humidity of 30% at room temperature. Further, it is revealed that the room‐temperature process MAPbI3 films show a near monoexponential decay pathway with a long photoluminescence lifetime of >400 ns. Abstract : By using chloroform‐assisted HCl method, smooth and full coverage MAPbI3 films are obtained at room temperature under ambient air condition (relative humidity, 30%). A maximum efficiency of 17.72% is achieved for the MAPbI3 solar cells fabricated via this method. Good reproducibility is demonstrated for the MAPbI3 solar cells when relative humidity during device fabrication is between 0% and 30%.